Estudo do potencial farmacoquímico do óleo de batiputá (Ouratea fieldingiana - Gardner Engl.) como insumo farmacêutico - Pinto, Talita Rocha de Miranda (2017)
Ouratea fieldingiana (Gardner) Engl., popularly known in the northeast as batiputá, is a plant, essentially arboreal or shrub, belonging to the family ochnaceae, genus ouratea. From its fruit can be extracted an oil that is used in both cooking and folk medicine as anti-inflammatory, healing and in the treatment of cough and flu states. It was observed that extracts and fractions obtained from plants belonging to the genus ouratea have important biological activities such as antitumor, antiviral, vasodilator, antimicrobial and inhibition of DNA topoisomerase, making evident the therapeutic potential of these species, which justifies the necessity of conducting a pharmacochemical study and to explore the pharmaceutical potential of the input from the fruits of the native species of Ceará’s state. The present work had the objective of conducting the pharmacochemical study of batiputá oil from the fruits of Ouratea fieldingiana in order to determine its chemical composition and obtaining a pharmaceutical input. For this, preliminary tests were carried out to select the most suitable technique for fruit desiccation, with determination of the moisture content. In order to characterize its quality parameters, a phytochemical approach was performed, evidencing the presence of alkaloids, catechins, coumarins, steroids, free phenols, flavonoids, saponins, anthraquinones and triterpenoids and analysis of their mineral and metallic composition, which revealed richness of micro and macro nutrients with important functions in the body. Subsequently, tests were carried out, where the quality specifications of the oil extracted by hand and laboratory were obtained as organoleptic and physico-chemical characteristics, such as: density, refractive index, acidity, saponification, esthers and iodine, obtained. The analysis of the chemical composition of the artisanal (AO) and laboratory (LO) oils by CG-FID evidenced the presence of the acid methyl ethers, palmitic, oleic and linoleic. The results obtained in this work were unpublished and provide scientific evidence of the feasibility of applying the batiputá fruits in nutraceutical and batiputá oil in dermo-cosmetics, which encourages the maintenance and propagation of popular knowledge through scientific verification.